Action of plant stimulants on growth of cucumber plants (Cucumis sativus L.) - Castro, Paulo R. C.; Moreti, Augusta C. C. C.; Toledo Filho, Manoel R.; Bernardes, Marcos S.; Silva Filho, Nivaldo L.; Peres Filho, Otavio (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1987)
This experiment was carried out to determine the effects of Triacontanol (0.5 g/l), Ergostim (2 ml/l), Atonik (0.5 ml/l) and Agrostemmin (1.25 g/l) on growth of cucumber plants 'Hibrido Caipira AG-207'. Cucumber plants were sprayed 7 days after sowing, under greenhouse conditions. Agrostemmin reduced plant height until 20 days after sowing. Atonik reduced plant height 27 days after sowing. At 34 days after cucumber sowing, plants treated with the plant stimulants not differed in height in relation to check treatment. Agrostemmin and Ergostim increased dry matter production of the lower part of the plant. The plant stimulants does not change the dry matter production of the apical region of cucumber plants.